Notes on the genus Berberis (Berberidaceae) in Mexico - Zamudio, Sergio (Instituto de Ecología, A.C., 2009)
Some historical errors related with the application of the names Berberis trifolia Schltdl. et Cham., B. ilicina Schltdl. and B. schiedeana Schltdl., which were assigned subsequently to the same entity, are clarified. Berberis trifolia is recognized as the valid name because it was the first one applied to the species. The type locality of this species is located near the border between the states of Puebla and Veracruz, between Cuauhtotolapa (La Gloria), municipality of Perote, Veracruz and Tlachichuca, municipality of Tlachichuca, Puebla. Berberis alpina Zamudio is described as a new species; it has been extensively confused with B. schiedeana (synonymous of B. trifolia); with which is not related. The correct identities of B. pallida Hartw. ex Benth. and B. hartwegii Benth. are determined, and lectotypes for B. hartwegii Benth., Mahonia paxii Fedde and M. zimapana Fedde are designated.